PROBLEMS OF TEACHING FOREIGN LANGUAGES AS A SECOND LANGUAGE - M. S. Khasanova (Journals Park Publishing, 2025)
This scientific article analyzes the problems in the process of teaching foreign languages as a second language. The article considers problems related to teaching methodologies, educational resources, teacher training, student motivation, as well as cultural and sociolinguistic factors. The article also provides suggestions and recommendations on how to overcome these problems, improve the quality of teaching, and covers modern approaches, technologies and their implementation in practice.
Keywords: Foreign languages, second language, teaching, methodology, learning resources, teacher training, student motivation, sociolinguistic factors, cultural factors, problems, language learning, modern approaches.